2018
DOI: 10.1097/hjh.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of baroreflex activation therapy (NEO) in patients with resistant hypertension

Abstract: Though there are common side effects, Barostim neo significantly lowers blood pressure in resistant hypertension and provides an adequate safety profile. Regular patient visits are necessary to register side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Nonetheless, the findings from these studies are consistent in that they show appreciable lowering of BP in patients with RHT after no less than 6-12 months of therapy. [55][56][57][58][59][60] Acute off transient increases in BP in response to brief device deactivation in patients with chronic BA confirm true BP lowering with the Barostim neo system. In addition, these studies have included patients with prior RDN and protracted HT.…”
Section: Clinical Studies With the Barostim Neo Systemmentioning
confidence: 76%
“…Nonetheless, the findings from these studies are consistent in that they show appreciable lowering of BP in patients with RHT after no less than 6-12 months of therapy. [55][56][57][58][59][60] Acute off transient increases in BP in response to brief device deactivation in patients with chronic BA confirm true BP lowering with the Barostim neo system. In addition, these studies have included patients with prior RDN and protracted HT.…”
Section: Clinical Studies With the Barostim Neo Systemmentioning
confidence: 76%
“…The Barostim Neo system (CVRx, Inc., Minneapolis, Minnesota), a second-generation carotid sinus electrical stimulation device, overcomes these disadvantages, has a longer battery life, requires unilateral carotid sinus peri-implantation of the stimulating electrodes, and has been shown to be effective in controlling hypertension in several clinical studies ( 173 175 ). Although the system has a high rate of AEs, with a small sample study showing mild local adverse effects in 97.6% of subjects, most of which can be resolved by adjusting the pulse transmitter settings ( 176 ). In addition to lowering BP, the BeAT-HF study confirmed that BAT with the Neo system was beneficial in patients with HFrEF.…”
Section: Other Regulation Methodsmentioning
confidence: 99%
“…Patients who had stage 3 or 4 CKD experienced a greater reduction in proteinuria, and the eGFR remained stable in the treated patients despite the reduction of systemic blood pressure. 30 The MobiusHD device (Vascular Dynamics, Mountain View, CA), another secondgeneration device, is a catheter-delivered self-expanding intracarotid implant designed to activate the barorefl ex (Figure 3). 31 In its fi rst study in humans, it seemed successful in reducing blood pressure, and a larger trial designed to evaluate the safety and effectiveness of the MobiusHD device is actively enrolling patients.…”
Section: Studies Of Barorefl Ex Activation Therapymentioning
confidence: 99%